2002
DOI: 10.1128/jvi.76.6.2952-2963.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Gene 10 (UL49.5) Product of Equine Herpesvirus 1 Is Necessary and Sufficient for Functional Processing of Glycoprotein M

Abstract: The functional cooperation of equine herpesvirus 1 (EHV-1) glycoprotein M (gM) and the gene 10 (UL49.5) product was analyzed. Transient-transfection experiments using gM and UL49.5 expression plasmids as well as RK13 cell lines constitutively expressing UL49.5 (RK49.5) or gM (RKgM) demonstrated that the endo-␤-N-acetylglucosaminidase H (endo H)-resistant mature form of gM was detectable only after coexpression of the two proteins. Deletion of the EHV-1 UL49.5-homologous gene 10 in strain KyA resulted in a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…From alphaherpesviruses to gammaherpesviruses, gM interacts with gN, and the complex typically leads to changes in intracellular targeting of either or both proteins (15,21,30,36,37,40). The present study indicates that this extends to HSV-1 and further reveals that the amino terminal 132 amino acids of HSV-1 gM are important for an efficient interaction between the two proteins.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…From alphaherpesviruses to gammaherpesviruses, gM interacts with gN, and the complex typically leads to changes in intracellular targeting of either or both proteins (15,21,30,36,37,40). The present study indicates that this extends to HSV-1 and further reveals that the amino terminal 132 amino acids of HSV-1 gM are important for an efficient interaction between the two proteins.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, while gN is dominant and alters the localization and/or maturation of gM in BHV-1, equine herpesvirus 1 (EHV-1), and HHV-8 (21,30,40), the opposite seems true for HSV-1, EBV, and infectious ILTV, where gM is required for the transport and/or processing of gN (this study) (36,37). While the reasons for this distinction among herpesviruses are not clear, that the complex formation has targeting consequences for gM or gN in all herpesviruses studied so far appears well conserved.…”
Section: Discussionmentioning
confidence: 99%
“…The UL49.5 ORF is relatively conserved among herpesviruses, and the interaction with gM is a common property of all UL49.5 homologs (36,42,48). So far, we have identified the UL49.5 homologs encoded by BHV1, PRV, and EHV1 as potent inhibitors of TAP.…”
Section: Discussionmentioning
confidence: 99%
“…It could be shown that MDV mutants lacking gB were nonviable; however, unlike other related viruses, MDV is unable to replicate in the absence of two major membrane protein complexes, the gE-gI and the gM-pU L 49.5 complex (61,62,67). While essentiality of gB has been shown for all herpesviruses analyzed thus far (53), most Alphaherpesvirinae are still able to grow in cultured cells in the absence of the other glycoproteins (2,3,22,32,37,51,56,77,78). Besides MDV, VZV is also an exception to the rule, because it requires expression of gE for growth in vitro and in vivo, while gI is required for VZV growth in Vero cells, but not in fibroblasts or melanoma cells (14,39,40,62).…”
mentioning
confidence: 99%